Evaluation of a Rapid Immunochromatographic Test for Detection of Streptococcus pneumoniae Antigen in Urine Samples from Adults with Community-Acquired Pneumonia - Murdoch, David R. (American Society for Microbiology, 2001)
Streptococcus pneumoniae is the most common cause of community-acquired pneumonia but is undoubtedly underdiagnosed. Isolation of S. pneumoniae from blood is specific but lacks sensitivity, while isolation of S. pneumoniae from sputum may represent colonization. We evaluated a new immunochromatographic test (NOW S. pneumoniae urinary antigen test; Binax, Portland, Maine) that is simple to perform and that can detect S. pneumoniae antigen in urine within 15 min. Urine samples from 420 adults with community-acquired pneumonia and 169 control patients who did not have pneumonia were tested. Urine from 315 (75%) of the pneumonia patients and all controls was tested both before and after 25-fold concentration, while the remaining 105 samples were only tested without concentration. S. pneumoniae urinary antigen tests were positive for 120 (29%) patients with pneumonia and for none of the controls. Of the urine samples tested with and without concentration, 96 were positive, of which 6 were positive only after concentration. S. pneumoniae antigen was detected in the urine from 16 of the 20 (80%) patients with blood cultures positive for S. pneumoniae and from 28 of the 54 (52%) patients with sputum cultures positive for S. pneumoniae. The absence of S. pneumoniae antigen in the urine from controls suggests that the specificity is high. Concentration of urine prior to testing resulted in a small increase in yield. The NOW S. pneumoniae urinary antigen test should be a useful adjunct to culture for determining the etiology of community-acquired pneumonia in adults.